Allergic Rhinitis and Its Associated Co‐Morbidities Among Patients Attending the ENT Department at Kilimanjaro Christian Medical Center in Northern Tanzania: Cross‐Sectional Study - Kenneth Mlay; Gasper Temba; Adrian Matasha; Pendael Mzonge; Denis Katundu; Desderius Chussi (Immunity, Inflammation and Disease)
ABSTRACT Introduction Allergic rhinitis is the specific inflammation against allergen by immune defense cells on the nasal mucosa, which can lead to chronic nasal symptoms such as sneezing, itching, runny nose, and nasal congestion. It is associated with high morbidity including sinusitis, asthma, otitis media, hypertrophied inferior turbinate, and nasal polyps. Despite its complications, it remains poorly recognized and tracked. Methods A cross‐sectional hospital‐based study was done, a total of 221 patients received Ear, Nose And Throat services at Kilimanjaro Christian Medical Center during the study period all patients with a clinical diagnosis of allergic rhinitis were captured; Data was collected using a pre‐tested coded questionnaire (Score For Allergic Rhinitis). The data was then analyzed using SPSS version 22. Results A total of 221 patients with a clinical diagnosis of allergic rhinitis were approached in a 6 months study period, 111 (50.2%) were females, and 140 (63.4%) were residing in urban areas. The prevalence of allergic rhinitis was 23.9%. Factors such as age OR 0.12, 95% CI (0.03; 0.40), education OR 0.13, 95% CI (0.04; 0.44), occupation OR 3.75, 95% CI (1.36; 10.32), adenotonsillar hypertrophy OR 4.66, 95% CI (2.21; 9.80), and OME OR 4.11, 95% CI (1.32; 12.83) (p = 0.009) were found to be significantly associated with allergic rhinitis. 60.4%, Inferior turbinate hypertrophy is the leading co‐morbidity of allergic rhinitis which accounts for 64.7%. Conclusion Allergic rhinitis is among the common health problems affecting Tanzanians. It is a commonly seen disorder in younger age ( < 15 years) which is in correlation with other studies done in Africa and worldwide.